Substitutes for leadership: alternative perspectives - Hussain, G. (Emerald Group Publishing Ltd., 2016)
Purpose: The purpose of this study is to explore alternative models of substitutes for leadership. These alternative models are a leadership-only model, substitutes for the leadership-only model and substitutes for the leadership-mediated-effects model. Design/methodology/approach: Four occupational groups were targeted, namely, PhD faculty of institutions of higher education, medical doctors who work in district headquarters’ hospitals, licensed pharmacists and certified engineers. Also, a self-administered questionnaire was used to collect data, and 523 usable responses were received. Findings: Partial least square path modeling was used for data analysis, and the results of structural models revealed that: the dimensions of transformational leadership significantly affected the followers’ outcomes; a few substitutes for leadership also significantly affected the followers’ outcomes; and, in some cases, substitutes for leadership significantly mediated the relationship between dimensions of transformational leadership and followers’ outcomes. Practical implications: Findings of the study provide useful implications to improve the managerial practices of organizational leaders, work design strategies in organizations and overall organizational policies for effective functioning. Other developing countries with similar socio-economic status may use these findings to improve organizational functioning. Originality/value: This study makes important contributions to the leadership literature. It tests three alternative models in the domain of substitutes for the leadership theory and tests the separate effects of dimensions of transformational leadership and substitutes for leadership on followers’ work outcomes. Further, it specifies the mediating effects of substitutes for leadership on the dimensions of transformational leadership and followers’ work outcomes. Most important, this study for the first time tests transformational leadership and substitutes for leadership concepts in Pakistani work settings and advances the theoretical and empirical literature in this local context.